PERSEPSI SISWA TERHADAP BUDAYA K-POP DI SMA NEGERI 13 MAKASSAR - Amir, Arfenti; Qalby, Mochammad Neor Alim; Ilelapotoar, Trence; Iskandar, Abdul Malik (Phinisi Integration Review, 2023)
. This study aims to determine the spread of K-Pop culture among students of SMA Negeri 13 Makassar, and compare diffusion theory with technological developments. This study used qualitative reserch with informants, grade 2 students, sociology teachers, representatives to schools, and the community. The date collection techniques used direct observation, in-depth interviews, and docummentation. Data was analyzed by reducing data and drawing conclusions. Based on the results of the study showed that the factors that influence students of SMA Negeri 13 Makassar to get to know K-Pop culture were also very halpful and add  to the exprience in the era of increasingly advanced globalization. Researchers also found an impact in the process of spreading K-Pop culture in Indonesia. Especially students of SMA Negeri 13 Makassar, namly positive impacts and negative impacts. The positive impacts of K-Pop culture included adding new insights, being able to increase vocabulary, learning outside culture, relieving stress, and motivating  fans. While the negative impact was lack of intereset in learning, waste, making them focus more on outside culture, play more, spend quota to watch Korean dramas and play social media.Penelitian ini bertujuan untuk mengetahui penyebaran budaya K-Pop di kalangan siswa SMA Negeri 13 Makassar, dan membandingkan teori difusi dengan perkembangan teknologi. Penelitian ini menggunakan penelitian kualitatif dengan informan siswa kelas XI, guru sosiologi, wakil kepala sekolah, dan masyarakat. Teknik pengumpulan data yang digunakan yaitu observasi langsung, wawancara mendalam, dan dokumentasi. Data dianalisis dengan mereduksi data dan menarik kesimpulan. Hasil penelitian menunjukan bahwa faktor yang mempengaruhi siswa SMA Negeri 13 Makassar untuk mengenal budaya K-Pop juga sangat membantu dan menambah pengalaman diera globalisasi yang semakin maju. Peneliti juga menemukan dampak dalam proses penyebaran budaya K-Pop di Indonesia, khususnya siswa SMA Negeri 13 Makassar yaitu dampak positif dan dampak negatif. Adapun dampak positif budaya K-Pop diantaranya menambah wawasan baru, dapat menambah kosakata, mempelajari budaya luar, menghilangkan stres, dan memberi motivasi terhadap para penggemar. Sedangkan dampak negatifnya adalah kurangnya minat belajar, pemborosan, membuat mereka lebih fokus ke budaya luar, lebih banyak bermain, menghabiskan kuota untuk menonton drama Korea dan bermain sosial media.